Purchasing Strategy and Its Impact on Raw Material Procurement in Manufacturing Companies - Novita, Dede; Santoso, Bambang (International Journals of Energy Economics and Financial Analysis (IJEEFA), 2025)
The purchasing division is an important part of the organizational structure in manufacturing companies. This division has an important responsibility and strategic role in supporting the smooth procurement of raw materials, especially in manufacturing companies. This is in the form of planning, coordination, and control in the process of procuring raw materials so that company operations can run optimally and according to specifications to support efficient production quality. This study aims to analyze how the role of the purchasing division in managing and supporting the availability of raw materials in manufacturing companies The research method used is descriptive qualitative method with a case study approach in one of the manufacturing companies Data collection was carried out through observation and interviews with purchasing staff directly to find out the procurement and management procedures for raw materials in the company. The results showed that the purchasing division staff in choosing suppliers, establishing good communication, and conducting periodic evaluations are the keys to success in ensuring the availability of raw materials quickly, precisely and efficiently. The main steps taken are daily recording, monitoring, and coordination with other divisions in determining the availability of raw materials in the company so that there are no obstacles faced such as delays in delivery, mismatches in specifications, and also the price of raw materials Therefore, careful planning and good management are important factors in improving company performance to face changes and challenges in the future so that the company can continue to grow.